Caracterização molecular do cancro do pulmão na população Portuguesa - Variantes acionáveis e Variantes não acionáveis - Cátia Sofia de Sousa Pereira (2023)
According to the World Health Organization (WHO), lung cancer has been the most common oncological disease, but also the deadliest. About 80% is associated with tobacco in its etiology. Adenocarcinoma (ADC) is the predominant histological type and, as other lung carcinomas, its distribution depends on demographic, environmental and behavioral factors. The molecular variants tend to accompany some of these variations and their predictive value can translate into considerable differences in the life quality and survival of patients, by dictating eligibility for targeted therapies. The purpose of the present work was to evaluate the involvement of certain genes in lung carcinogenesis as well as the incidence of actionable (VAc) and non-actionable (VnAc) variants in the Portuguese population. In a retrospective study, the data of 1987 patients previously anonymized was admitted. The data included demographic and clinicopathological information as well as the molecular analyses obtained by sequencing of their sampled lung carcinomas via the Oncomine Focus Assay panel (Thermo Fisher Scientific, Cat. No. A28548). Statistical analysis was performed at a significance level of 0,05 using the Statistical Package for the Social Sciences Statistics (IBM SPSS Statistics for Windows, Version 28.0. Armonk, NY: IBM Corp). The patients were predominantly male (63,1%). Smoking history was underlying 72,4% of the cases and its active consumption resulted in a lower average age (61,6 ± 9,8 years). The most common histological type was ADC (89,3%). The mutated genes and their variants were distributed differentially depending on histological type, gender and smoking habits. KRAS (26,5%), EGFR (23,3%) and MET (6,4%) were the most recurrently altered genes. Gene amplifications and MET skipping were more prevalent in squamous cell carcinoma, while rearrangements were more common in women and non-smokers. In cases with VAc, EGFR, KRAS and MET would be likely therapeutic targets in 44,5%, 21,1% and 12,4%, respectively. In 8,5% of the samples, VAc were accompanied by variants compatible with on-target resistance mechanisms and 121 off target variants could be indicated as possible causes of tumor progression. Additionally, PD L1 expression and molecular variants were correlated, namely CTNNB1 and EGFR variants were more frequent in samples with PD-L1<50% and KRAS and MET in samples with PD-L1≥50%. In conclusion, (1) the results were mostly consistent with reported data in western lung carcinomas; (2) targeted therapy could currently be an option for at least half of patients with advanced lung disease in Portugal; and (3) in the near future, somatic molecular analysis could expand its purposes as well as the recommended gene panel.